The NEWT platform: an extensible plugin framework for creating ReSTful HPC APIs‡. (29th July 2015) - Cholia, Shreyas; Sun, Terence
Summary: This work describes the NEWT platform, a framework for creating ReSTful web APIs for high‐performance scientific computing. The NEWT platform is designed to be a customizable framework that can be deployed at a high‐performance computing center and enables access to various backend resources and services through a common web API. The goal of this effort is to create a service that can be plugged into multiple backend resources and can easily be extended while presenting a standard interface to the consumer with common semantics. This effort also updates the NEWT API that has been deployed at the National Energy Research Scientific Computing Center since 2010 and provides additional structure and consistency across the API. Copyright © 2015 John Wiley & Sons, Ltd.